SHARING SACRED SPACES IN THE MEDITERRANEAN: CHRISTIANS, MUSLIMS, AND JEWS AT SHRINES AND SANCTUARIES. - Gourlay, William (The Levantine Review, 2012)
Review of: Sharing Sacred Spaces in the Mediterranean: Christians, Muslims and Jews at Shrines and Sanctuaries. By Dionigi Albera and Maria Couroucli (editors), Indiana University Press, 2012, Cloth, 288 pp. 70.00 ISBN 9780253356338